DISTRIBUTION OF HEAVY METALS IN SOIL IN INDUSTRIAL ESTATES: A COMPARATIVE REVIEW OF SOUTH CHINA AND SIDOARJO, EAST JAVA, INDONESIA - Diana Rinawati; Raldi Hendro Toro Seputro Koestoer; Khayan Khayan (Universitas Brawijaya, 2023)
Environmental pollution caused by heavy metals can be found in various media, both soil, water and air, and these components occur in very small particles. The selected study locations are located near areas with intensive industrial activities, in the coastal areas of southern China and other industrial areas in Sidoarjo Regency, East Java, Indonesia. In both locations there are similarities, in terms of the characteristics of the soil industry with the parameters of heavy metals Pb, Cd, Zn, Cu. The difference lies in the depth of the soil sample taken. In China, soil samples were taken at the soil surface (0-20) cm and below the soil surface (20-40) cm, while in Sidarjo Regency only at the soil surface (0-20). ) cm. The number of samples taken in South China is greater than in Sidoarjo. Comparing the results of the South China and Sidoarjo industrial areas, it was found that there were differences in the heavy metal content in polluted soil, that heavy metals are produced from natural and anthropogenic sources such as natural weathering, fertilizer application, and transportation. The origin of Hg, Cd, Ni, and Pb probably comes from human activities such as excessive use of pesticides and fertilizers, while Pb probably comes from vehicle exhaust. The heavy metal content of Cadmium (Cd) is dominant in the soil of South China, while in Sidoarjo, East Java, Indonesia, the content of heavy metals is mainly Lead (Pb) and Mercury (Hg).